Monastery Memorable Tourism Experiences in Greece: An Empirical Study on Gender Differences - Irene (Eirini) KAMENIDOU; Aikaterini STAVRIANEA; Aikaterini VASSILIKOPOULOU; Spyridon MAMALIS (Communications of International Proceedings, 2022)
Memorable tourism experiences are studied through quantitative research focusing specifically on experiences from monastery tourism and exploring existing gender differences from the seven dimensions of the memorable tourism experience scale. Field research is conducted referring to one monastery complex the Meteora and the new Panagia Soumela monastery in Imathia, Greece. Through an online questionnaire, a sample of 228 monastery tourists was collected employing a non-probability sampling method for study participation. Gender differences examined on the seven dimensions of memorable tourism experiences with independent sample t-tests, provided with statistically significant differences for two dimensions: Hedonism and Knowledge.  Based on results, communication and marketing directions are suggested to improve tourists’ monastery memorable tourism experiences.
Keywords: Memorable Tourism Experiences; Monastery Tourism; Gender Differences; Marketing; Communication